Kemitraan Kelompok Tani dan Pedagang dalam Pemasaran Sagu di Kota Kendari Sulawesi Tenggara Indonesia - Nikoyan, Anas; Abdullah, Sukmawati; Rahmayanti, Miftha (Department of Agribusiness, Halu Oleo University, 2021)
This study aims to determine what role farmer groups have in sago marketing partnerships in Labibia Village, Mandonga District, Kendari City. This study was placed in Labibia Village, Mandonga District, Kendari City, from June to November 2020. Descriptive analysis and income formulas are used in the research. This study shows that the role of farmer groups is as a forum for learning by obtaining information on costs, market needs, information on business actors, and establishing partnerships. As a vehicle for cooperation, fellow farmers process sago in cooperation and market their production and output in groups, collaborating with sago business actors, namely Mandonga market traders, Small Kiosks, and UD. Sinar Fajar and obtain market certainty and a fixed selling price. It provides production facilities for sands, grate machines, and water pumps through group cost-sharing as production units. The rules of the cooperation contract are to ensure market certainty and the selling price of farmer groups and supply for sago business actors per month, impose unwritten sanctions, fulfill needs by supplying sago to partner business actors, maintain the white quality of sago, sustainably meet needs.